Phylogeny and taxonomy of the patagonian miocene Falcon Thegornis musculosus Ameghino, 1895 (Aves: Falconidae) - Noriega, Jorge Ignacio (2011)
The fossil record of the family Falconidae is poor and fragmentary. Extinct representatives from South America include the late early Miocene (Santacrucian) Thegornis musculosus and Thegornis debilis. Both species were originally described as Falconidae and afterwards moved to Accipitridae Circinae or Buteoninae. The analysis of a very well preserved and complete specimen of T. musculosus with similar stratigraphic and geographic provenances of the type material (lower levels of Santa Cruz Formation, coast of Patagonia, Argentina) corroborates the validity of the genus and its falconid affinities. The skull and postcranial morphology exhibit strong resemblances with the open-savannah inhabiting Herpetotheres and the forest-dwelling Micrastur (Herpetotherinae) but differ substantially from Falconinae (Falconini plus Caracarini). Detailed comparisons with a broad arrange of falconiform taxa in a cladistic framework, confirm its phylogenetic placement within the Herpetotherinae and sister to H. cachinnans. The ecotonal margins produced by the vanishing of humid forests that developed during changes in Patagonian plant communities throughout early Neogene times are hypothesized as a plausible scenario to understand the evolution of this basal clade of falcons.